Effectiveness of Handheld Fan as A Non-Pharmacological Therapy in Reducing Dyspnea: A Scoping Review - Sandra Aprilia Putri; Ricky Putra Liyan; Nabilla Ramadhani; Gaviota Khalish; Chairul Huda; Romy Suwahyu (Athallah Publishing, 2026)
Chronic conditions such as chronic obstructive pulmonary disease, heart failure, and cancer can disrupt daily activities and reduce quality of life. One frequently used non-pharmacological intervention is the handheld fan, which is a handheld fan directed at the face to provide airflow that can help reduce the perception of shortness of breath through trigeminal receptor stimulation. Purpose: This journal review was conducted to determine the extent to which a handheld fan is effective in reducing complaints of shortness of breath in various clinical conditions through a scoping review approach. Methods: This review was conducted by searching and reviewing research articles from Google Scholar, PubMed, and national journals in the period 2021–2025 using the PICO framework, which includes a patient population with shortness of breath, handheld fan intervention, a control group comparison or no comparison, and outcomes in the form of a reduction in dyspnea levels. A total of 10 articles met the inclusion criteria and were analyzed descriptively. Results: The use of a hand-held fan for 5–10 minutes at a distance of 15–30 cm was consistently effective, demonstrating a reduction in shortness of breath in patients with chronic disease. No adverse effects were observed in all studies. Therefore, a handheld fan is considered safe, easy to implement, and potentially helpful in managing dyspnea.